An IV Hazard Model of Loan Default with an Application to Subprime Mortgage Cohorts - Palmer, Christopher J. (National Bureau of Economic Research, 2023)
This paper develops a control-function methodology accounting for endogenous or mismeasured regressors in hazard models. I provide sufficient identifying assumptions and regularity conditions for the estimator to be consistent and asymptotically normal. Applying my estimator to the subprime mortgage crisis, I quantify what caused the foreclosure rate to triple across the 2003-2007 subprime cohorts. To identify the elasticity of default with respect to housing prices, I use various home-price instruments including historical variation in home-price cyclicality. Loose credit played a significant role in the crisis, but much of the increase in defaults across cohorts was caused by home-price declines unrelated to lending standards, with a 10% decline in home prices increasing subprime mortgage default rates by 50%
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Wohnimmobilien; Immobilienpreis; Hypothek; Kreditrisiko; Subprime-Krise; Insolvenz; IV-Schätzung; USA; Instrumental Variables (IV) Estimation; Duration Analysis; Optimal Timing Strategies; Financial Crises; Banks; Depository Institutions; Micro Finance Institutions; Mortgages; Housing Supply and Markets; Government Policy